2009
DOI: 10.3109/15368370902918912
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mobile-Phone Electromagnetic Fields on Brain Electrical Activity: A Critical Analysis of the Literature

Abstract: We analyzed the reports in which human brain electrical activity was compared between the presence and absence of radio-frequency and low-frequency electromagnetic fields (EMFs) from mobile phones, or between pre- and post-exposure to the EMFs. Of 55 reports, 37 claimed and 18 denied an EMF-induced effect on either the baseline electro encephalogram (EEG), or on cognitive processing of visual or auditory stimuli as reflected in changes in event-related potentials. The positive reports did not adequately consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 81 publications
(211 reference statements)
0
5
0
Order By: Relevance
“…In this paper we dealt with the criticism that was raised in the past, that the application of pulsed RF would lead to artefacts in the EEG and that the spectral energy of these spikes can be folded into the EEG recording, thus erroneously suggesting an EMF effect in the brain 18 . In the phantom experiment we showed that this is not the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we dealt with the criticism that was raised in the past, that the application of pulsed RF would lead to artefacts in the EEG and that the spectral energy of these spikes can be folded into the EEG recording, thus erroneously suggesting an EMF effect in the brain 18 . In the phantom experiment we showed that this is not the case.…”
Section: Discussionmentioning
confidence: 99%
“…A common criticism directed towards previous EMF studies is the complexity of the employed statistical methods. Marino et al 18 even suggest that ‘many claims result from the use of data-mining to make meaning from the data’. In this work we perform a statistical analysis using a Bayesian approach to counteract this criticism.…”
Section: Introductionmentioning
confidence: 99%
“…The research field is broad since several areas are explored, ranging from carcinogenesis and infertility to basic effects on physiological parameters. In general, results are conflicting and inconclusive (86)(87)(88)(89). While a number of studies demonstrate influence of radiation on health, others cannot replicate these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these methodological aspects, it has been suggested that source of funding might influence the results (63). It has been shown that 87% of brain activity studies are sponsored by the mobile phone industry (87). Although this does not necessarily imply that the results of these articles are biased, the issue of conflict of interest cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation